2017
DOI: 10.1155/2017/1432037
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Illumination on Ocular Status Modifications Induced by Short-Term 3D TV Viewing

Abstract: Objectives. This study aimed to compare changes in ocular status after 3D TV viewing under three modes of illumination and thereby identify optimal illumination for 3D TV viewing. Methods. The following measures of ocular status were assessed: the accommodative response, accommodative microfluctuation, accommodative facility, relative accommodation, gradient accommodative convergence/accommodation (AC/A) ratio, phoria, and fusional vergence. The observers watched 3D television for 90 minutes through 3D shutter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…An additional investigation determined that both the illumination mode and the utilisation of 3D viewing had an impact on ocular health ( Jiang et al 1991 ). This could be attributed to variations in luminance at the viewer’s position, the orientation of the light source, or the familiarity of the participants with their viewing surroundings ( Chen et al 2017 ). They suggested that front illumination is a favourable option for enhancing the visibility of 3D displays.…”
Section: Discussionmentioning
confidence: 99%
“…An additional investigation determined that both the illumination mode and the utilisation of 3D viewing had an impact on ocular health ( Jiang et al 1991 ). This could be attributed to variations in luminance at the viewer’s position, the orientation of the light source, or the familiarity of the participants with their viewing surroundings ( Chen et al 2017 ). They suggested that front illumination is a favourable option for enhancing the visibility of 3D displays.…”
Section: Discussionmentioning
confidence: 99%